Imagined eye cue increased altruistic behavior toward charity instead of stranger - Lv, Jieyu; Zhang, Yuanya; Shen, Yuxin; Weng, Xuedong; Xu, Liang (Frontiers in Psychology, 2025)
Previous research has not established a significant link between imagined eye cue and altruistic behavior, nor has it verified whether a sense of being seen played a role in it. This study employed a between-subjects design with a single factor (Cue Type: Imagined Eye Cue/Imagined Flower Cue/No Cue) to explore the impact of imagined eye cue on individuals' altruistic behavior in two different dictator games, and also assessed the mediating role of a sense of being seen. It revealed that participants who was presented with imagined eye cue acted more altruistically than those who was presented with imagined flower cue or no cue when the recipient of the dictator game was a charity. Although imagined eye cue strengthened participants' a sense of being seen, this sense did not mediate the relationship between cue type and altruistic behavior. The findings suggest that the imagined eye cue may encourage individuals to donate generously by stimulating their internal social norms. This provides a theoretical rationale for the normative mechanisms underlying the watching eyes effect and explores a more cost-effective and accessible approach for interventions aimed at promoting charitable behavior.